Planejamento temático baseado em tarefas no ensino de inglês para crianças: percurso reflexivo e analítico de uma professora - Périco, Ana Gabriela (Universidade Federal de São Carlos, 2018)
This work aims at designing, implementing, and analysing a thematic task-based material for a first grade group of kids from a public school. It was used in 2016 and its theme is Fairy Tales. It covers three stories: Puss in boots, Jack and the beanstalk and The story of the three little pigs. The material is predominantly made of tasks, but there are some ludic activities involving cutting and sticking, finger puppets and bean planting. Most of the tasks are one-way tasks (ELLIS, 2003), which were very suitable for the still egocentric behaviour of the students, aged between 6 and 7. Most of them were also closed tasks (ELLIS, 2003), which suited well to the beginners’ level, due to its highest necessity of management. The tasks were designed according to the principles of the Theme-Based Language Instruction, inserted in the Content-Based Instruction (CBI), Prabhu’s (1987) Task-Based Language Teaching (TBLT) and some Willis and Willis’s (2007) tasks. The junction of Theme-Based Instruction and Task-Based Language Teaching has originated the Thematic Task-Based Syllabus (TTBS). The methodology is qualitative-interpretive and inserted in an ethnographic groundwork (MOITA LOPES, 1996). The data were collected with the teacher-researcher’s journal, two questionnaires, an interview with the official English teacher, students’ drawings and video recordings. Two new tasks were identified: pictorial tasks and survey tasks. Both have suited the group very appropriately, making them use the foreign language interactively and in a ludic way. Results show a production of short and small speech turns in the target language, as well as the TTBS being responsible for a less automatic and a more comprehensive learning.
Thematic task-based syllabus and english teaching for kids: the reflective and analytcal journey of a teacher
Keywords: Tarefa; Planejamento Temático Baseado em Tarefas; Ensino de inglês para crianças; Elaboração de material didático; Contos de fada; Task; Thematic Task-Based Syllabus; English for kids; Materials design; Fairy Tales; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUAS ESTRANGEIRAS MODERNAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA